Learning Strategies at SMP Muhammadiyah 4 Gempol during the Covid-19 Pandemic - Fatmakiyyah Fatmakiyyah; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to analyze the learning strategies at SMP Muhammadiyah 4 Gempol during the Covid-19 pandemic that were applied by the teachers. In the research process this time using descriptive qualitative research methods. A qualitative approach is a research process to understand social or human problems by analyzing words to create a complex and comprehensive picture, and reporting detailed views of information obtained from sources of information in a natural environment. This study aims to reveal and conclude how the learning strategies are carried out by teachers at SMP Muhammadiyah 4 Gempol in this Covid-19 era. Which during this pandemic period, the learning process is carried out in two ways, namely online and offline. Among the strategies adopted by teachers in dealing with learning during the COVID-19 pandemic is that teachers must pay more attention to their pedagogical competencies when teaching students, then optimize them in teaching students who have difficulty learning in the midst of this pandemic. Also the teachers apply in some ways or strategies about learning from home in a better and creative way.